Collections of Views from Stakeholders on Public Facilities in Kajang: An Islamic Guide - Rosni, Nur Aulia (Journal of Architecture, Planning and Construction Management, 2020)
The paper attempts to discussion the provision of public facilities in the Kajang Local Plan 2020 based on the views and perspectives of the stakeholders. The research on development plan implementation issues was inspired during Town Planning Day Conference 2012 that was organized by Malaysia Institute of Planners when some of the speakers have highlighted the weakness of Malaysia development plan implementation due to (i) constant complaint of inefficient local plan implementation as development blue print, (ii) Lack of awareness of other government agencies and (iii) the review of local plan is timely in order to make the plan as strategic plan. Throughout the literature review process, researchers has found out that the implementation topic has receive less attention from the researcher, practitioner as well as decision maker compared to the preparation of plan or public participation issues. MPKJ Local Plan 2020 was selected due to its status as the latest gazette local plan in Selangor. The data collected was analyzed by using SPSS software and several analysis methods were adopted to generate the findings. From research findings, some recommendations will be generated based on the Islamic Planning principles. In general, the result shows that most of public facilities type in MPKJ Local Plan was successfully provided and able to cater the current needs of the local community. However, the provision of public facilities policies in the local plan need to be revise in order to cater the demand of Kajang rapid population growth.